A new method to elicit and measure movement illusions in stroke by means of muscle tendon vibration: the Standardized Kinesthetic Illusion Procedure (SKIP). (2nd January 2020) - Beaulieu, Louis-David; Schneider, Cyril; Massé-Alarie, Hugo; Ribot-Ciscar, Edith
Abstract: Purpose: Muscle tendon vibration (MTV) strongly activates muscle spindles and can evoke kinaesthetic illusions. Although potentially relevant for sensorimotor rehabilitation in stroke, MTV is scarcely used in clinical practice, likely because of the absence of standardised procedures to elicit and characterise movement illusions. This work developed and validated a Standardised Kinaesthetic Illusion Procedure (SKIP) to favour the use of MTV-induced illusions in clinical settings. Materials and methods: SKIP scores were obtained in 15 individuals with chronic stroke and 18 age- and gender-matched healthy counterparts. A further 13 healthy subjects were tested to provide more data with the general population. MTV was applied over the Achilles tendon and SKIP scoring system characterised the clearness and direction of the illusions of ankle dorsiflexion movements. Results: All healthy and stroke participants perceived movement illusions. SKIP scores on the paretic side were significantly lower compared to the non paretic and healthy. Illusions were less clear and sometimes in unexpected directions with the impaired ankle, but still possible to elicit in the presence of sensorimotor deficits. Conclusions: SKIP represents an ancillary and potentially useful clinical method to elicit and characterise illusions of movements induced by MTV. SKIP could be relevant to further assess the processing of proprioceptive afferents in stroke and their potential impact on motor control and recovery. It may be used to guide therapy and improve sensorimotor recovery. Future work is needed to investigate the metrological properties of our method (reliability, responsiveness, etc.), and also the neurophysiological underpinnings of MTV-induced illusions.